The Impact of Intestinal Ultrasound on the Management of Inflammatory Bowel Disease: From Established Facts Toward New Horizons - Nardone, Olga Maria; Calabrese, Giulio; Testa, Anna; Caiazzo, Anna; Fierro, Giuseppe; Rispo, Antonio; Castiglione, Fabiana (Frontiers in Medicine, 2022)
Intestinal ultrasound (IUS) plays a crucial role as a non‐invasive and accurate tool to diagnose and assess inflammatory bowel disease (IBD). The rationale of using IUS in Crohn’s disease (CD), a transmural disease, is widely acknowledged. Whilst the use of IUS in ulcerative colitis (UC) being a mucosal disease, is often underestimated but recently it is increasingly expanding. In the context of treat to target approach, the role of IUS is shifting toward a monitoring tool for predicting response to therapy. Hence, adjusting therapeutic approaches based on IUS response could reduce the burden related to endoscopy and speed decision process with the ultimate goal to alter the natural course of IBD. Assessment of bowel wall thickness (BWT) is the most reliable IUS measure. However, development of validated and reproducible sonographic scores to measure disease activity and the identification of parameters of therapeutic response remain a relevant issue to implement the daily adoption of IUS in clinical practice. Accordingly, this review will focus on the current literature investigating the impact of IUS on CD with emphasis on the concept of transmural healing (TH) and the main related advantages. We further explored new insights on the role of IUS in UC and its clinical implications.